Law Without Lawyers: Examining the Limitations of Consumer-Centric Legal Tech Services (Journal of Intellectual Property and Information Technology Law (JIPIT), 2023)
The legal field is undergoing a disruptive change with the emergence of technology- based legal services aimed directly at serving the consumer, bypassing the need for a human lawyer. Specialized legal technologies powered by Artificial Intelligence (AI) or enabled by blockchain are leading to what is being referred to as new law, new ways of interpreting, implementing, and enforcing the law. Raymond Brescia has termed this transformative period in legal history as the third wave of lawyering. This wave is characterized by a new world of law without lawyers, comparable to the banking revolution, where mobile apps and online banking platforms replaced traditional tellers. There is an emergence of a legal ecosystem where conventional legal practices coexist alongside technology-driven legal services. These legal techs hold the promise of enhancing legal and justice inclusion by providing cheaper, more convenient, and more accessible legal services compared to traditional law firms and lawyers. This paper examines the emerging legal tech field, focusing on the business- to-consumer (B2C) category.B2C legal tech refers to tools designed to provide legal services and information directly to consumers without requiring the involvement of a human lawyer. This paper explores the factors driving these disruptive changes in legal services and evaluates some of the limitations of legal tech in meeting clients’ legal needs. The author concludes that B2C legal tech is gaining traction. However, the author avers that these technologies have limitations in fully meeting the needs of their users; therefore, lawyers still play an essential role in the legal ecosystem. As legal tech continues to gain traction, specific measures need to be implemented to address some of their limitations and ensure the seamless integration of these technologies into the legal field. This paper contributes to the ongoing discourse on the future of the legal profession in the era of technological advancement.